2020 AHA/ACC Key Data Elements and Definitions for Coronary Revascularization: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Data Standards (Writing Committee to Develop Clinical Data Standards for Coronary Revascularization). Issue 4 (April 2020) - Dehmer, Gregory J.; Badhwar, Vinay; Bermudez, Edmund A.; Cleveland, Joseph C.; Cohen, Mauricio G.; D'Agostino, Richard S.; Ferguson, T. Bruce; Hendel, Robert C.; Isler, Maria Lizza; Jacobs, Jeffrey P.; Jneid, Hani; Katz, Alan S.; et al.
Abstract : Supplemental Digital Content is available in the text.